Four-armed Shaiva figure in the Government Museum at Sikar - Temples of India Project Team (Jio Institute, 2024)
This Shaiva figure was possibly part of a devakostha or sculptural niche placed on the walls of a now-lost Shaiva shrine. It is now housed in the Government Museum, Sikar. The four-armed seated figure holds a trident and a staff in the upper two hands, while the lower two hands are considerably damaged. The figure is ithyphallic, symbolizing the Urdhvareta aspect of Shiva, indicating mastery over the vital energies through ascetic vigour. It is plausible that this image represents Lakulisha, the preceptor of the Pashupata tradition. The Harshnath Temple’s history clearly indicates that the temple was under the control of and likely erected by ascetics of the Lakulisha-Pashupata tradition. Therefore, the depiction of Lakulisha on the temple walls comes as no surprise.